Treenighed og gudbilledlighed - Pedersen, Kim Arne (Grundtvig-Studier, 1992)
Trinity and Man as an Image of God. By Kim Arne Pedersen Regin Prenter: »Grundtvig’s Doctrine of the Trinity. In: N.F.S. Grundtvig Theologian and Teacher of The Church«. Published by the Committee for Church and Theology, 1983 (out of sale). »The View of the Church«. Published by the Committee for Church and Theology, on commission by the publishing firm Savanne, Christiansfeld, 1983. This review compares Professor, dr. theol. Regin Prenter’s late works on Grundtvig with the Danish theological traditions of this century. Although Prenter doesn’t intend to discuss the modern interpretations of Grundtvig, he indirectly polemicizes against Kaj Thaning’s and K.E. Løgstrup’s readings of Grundtvig as separating Christianity and human life, understanding life as created and because of that free to be lived on its own conditions. Opposite this tradition, which is inspired by Secularisation theology and is an important part of Danish Creation theology, Prenter emphasizes that the true human life is a Christian life, reborn in baptism and flourishing from the Eucharist. Human life follows a Trinitarian structure and the incarnation reunites the human life with the divine Trinity. Although Prenter criticizes Danish Creation theology, he also agrees with this tradition in stressing that human life has to be based on thrust in God as Creator and Father. Prenter interprets the divine Trinity as a personal living relationship between God as Father and God as Son, which implies a dimension of knowledge. Because of this dimension of knowledge, Prenter – like the Danish Creation theology - is aware of the metaphysical theme in Grundtvig’s theology. The reviewer agrees with Prenter in stressing this theme, but at the same time criticizes him for finding the roots of Grundtvig’s Trinitarian structure in Grundtvig’s Augustine readings and not in Grundtvig’s - critical - interactions with the philosophy of Schelling. In his attack on Schelling Grundtvig develops a Trinitarian structure based on man’s faculties of knowledge and founded in the aseite’of God as Father. Being aware of this, Prenter was able to expound also the ontological motives in Grundtvig’s theology.